2016
DOI: 10.1016/j.biocon.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

To what extent could edge effects and habitat fragmentation diminish the potential benefits of land sparing?

Abstract: Land sharing and land sparing are contrasting proposals for minimising the impacts of agriculture on wild species. Edge effects (biophysical gradients near habitat boundaries) might reduce population sizes on spared land, particularly in highly-fragmented landscapes, so might change conclusions about whether land sparing or land sharing is better for species' persistence. We assessed this possibility by modelling the population sizes of 120 Ghanaian bird species in the presence of a range of hypothetical edge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Furthermore, trait abundances conserved under land sparing declined markedly under high production scenarios, where spared lands represent only a small proportion of the landscape. This result supports findings of other studies, emphasizing the importance of sparing large blocks of natural habitat for effective biodiversity conservation via land sparing (Edwards et al, ; Gilroy, Woodcock et al, ; Lamb, Balmford, Green, & Phalan, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, trait abundances conserved under land sparing declined markedly under high production scenarios, where spared lands represent only a small proportion of the landscape. This result supports findings of other studies, emphasizing the importance of sparing large blocks of natural habitat for effective biodiversity conservation via land sparing (Edwards et al, ; Gilroy, Woodcock et al, ; Lamb, Balmford, Green, & Phalan, ).…”
Section: Discussionsupporting
confidence: 90%
“…Lamb et al () showed that for Ghanaian birds the relative benefits of sparing versus sharing are partially influenced by habitat quality, with land sharing marginally outperforming land sparing when spared lands constitute severely fragmented landscapes and suffer acute edge effects. Because rare and disturbance‐sensitive species are most likely to be affected by fragmentation (Banks‐Leite, Ewers, & Metzger, ) and contribute disproportionately to FD by possessing unique traits necessary for ecosystem function (LeitĂŁo et al, ), fragmentation effects could be especially important in degrading the value of sparing for FD.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, if species are strongly impacted by forest loss, then land sparing will be less harmful as it minimises natural habitat loss while intensifying production elsewhere (Edwards et al., ; Paul & Knoke, ; Phalan et al., ). The relative benefits of sparing and sharing will also vary with the effects of landscape structure: land sparing is likely to be less harmful if forest fragmentation has large negative impacts on biodiversity (Gilroy, Edwards, Medina, Haugaasen, & Edwards, ; Green et al., ; Lamb, Balmford, Green, & Phalan, ). However, the exact impacts of fragmentation are unclear (Fahrig, ), and it is possible that a land sharing approach that conserves highly fragmented habitats could be less harmful.…”
Section: Introductionmentioning
confidence: 99%
“…The relative benefits of sparing and sharing will also vary with the effects of landscape structure: land sparing is likely to be less harmful if forest fragmentation has large negative impacts on biodiversity (Gilroy, Edwards, Medina, Haugaasen, & Edwards, 2014;Green et al, 2005;Lamb, Balmford, Green, & Phalan, 2016). However, the exact impacts of fragmentation are unclear (Fahrig, 2017), and it is possible that a land sharing approach that conserves highly fragmented habitats could be less harmful.…”
Section: Introductionmentioning
confidence: 99%
“…The original formulation of the land sparing-sharing framework omits some complexities, but it can be and already has been modified to incorporate many of these, including spatial configuration and the influence of edge effects [60,61]; the influence of changing diets and reducing food waste [50]; inclusion of some ecosystem services [4,7,50,62]; prediction of the effects of specific public policies [63]; and application to forestry [64,65], urban planning [66][67][68][69] and marine conservation [70]. It is a model, and so all assumptions can be varied and tested.…”
Section: What Does the Model Not Do?mentioning
confidence: 99%